(untitled) (Research, Society and Development, 2022)
Aim: To analyze the cost of three bed bath technologies in critically ill cardiac patients. Study design: Non-participant, prospective, observational, and cost assessment study. Data were collected between February and August 2017, at the cardiac intensive care (ICU) of a university hospital. The convenience sample corresponded to 18 patients in the immediate postoperative period of cardiac surgery. Data were collected within 72 h after cardiac surgery, with 24-hour washout between baths. Project was approved under the number: 1.823.316. Results: The mean time for bed bath was 39.00±15.00 min (traditional bath), 33.00±12.24 min (distilled water bath) and 25.28±7.35 min (disposable bath). The average final costs identified were R 45.47 (US 8.80), R 40.78 (US 7.89) and R 48.36 (US 9.36). Conclusion: The bath with the lowest total average cost was the distilled water bath. The cost category that most burdens the bed baths is human capital, which represents more than 2/3 of the procedures total cost. There are few studies exploring the costs associated to nursing procedures, and this analysis can contribute to discussions about materials purchase and support managers to make better decisions about nursing care.